Merger Auditor dan Kualitas Audit: Bukti Empiris Dari Bursa Efek Indonesia - Sansaloni Butar-Butar (Jurnal Ekonomi dan Bisnis, 2016)
Merge rof Pricewaterhouse and Coopers & Lybrands that occurred in 1998 creates PricewaterhouseCoopers as the biggest accounting firm in history. Conceptually and supported by previous empirical result firm size is expected to be positively correlated with audit quality. Large accounting firms have financial ability to improve its auditors skill and can act more independently because major part of their income do not come from one or two clients. They spend huge investment in audit technology as well. However, this positive relationship only applies to environments where punishment is strictly imposed on audit failure. Unlike their counterparts in the United States and Europe, auditors working in Indonesia rarely face legal issues related to the audit assignment. In addition, empirical studies in Indonesia have always classified local auditors as Big N auditors if they affiliate with one of Big N auditors assuming same quality with that of Big N auditors. This assumption does not necessarily hold. Therefore, in the context of Indonesia environtments, this study predicts PricewaterhouseCoopers merger does not affect the quality of the audit. Using abnormal accruals as a proxy for audit quality, the results show that after the merger audit quality has declined significantly.